Selection of isomerization pathways of multistep photoswitches by chalcogen bonding - Shuaipeng Jia; Hebo Ye; Peng He; Xin Lin; Lei You (Nature Communications, 2023)
Abstract Multistep photoswitches are able to engage in different photoisomerization pathways and are challenging to control. Here we demonstrate a multistep sequence of E/Z isomerization and photocyclization/cycloreversion of photoswitches via manipulating the strength and mechanism of noncovalent chalcogen bonding interactions. The incorporation of chalcogens and the formyl group on open ethene bridged dithienylethenes offers a versatile skeleton for single photochromic molecules. While bidirectional E/Z photoswitching is dominated by neutral tellurium arising from enhanced resonance-assisted chalcogen bonding, the creation of cationic telluronium enables the realization of photocyclization/cycloreversion. The reversible nucleophilic substitution reactions further allow interconversion between neutral tellurium and cationic telluronium and selection of photoisomerization mechanisms on purpose. By leveraging unique photoswitching patterns and dynamic covalent reactivity, light and pH stimuli-responsive multistate rewritable materials were constructed, triggered by an activating reagent for additional control. The results should provide ample opportunities to molecular recognition, intelligent switches, information encryption, and smart materials.